The Best Biclique Cryptanalysis of the Lightweight Cipher FUTURE - Carvalho, G. C. de; Kowada, L. A. B. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2024)
In the past decade, lightweight cryptography has been of much interest in the academy, especially in regards to the cryptanalysis of such ciphers. The National Institute of Standards and Technology (NIST) is one of the responsible for this interest, given that they promoted in 2019 a public process to choose the American standard for lightweight cryptography. In 2022, the FUTURE cipher was published and has since been the target of much cryptanalysis, including integral, meet-in-the-middle and differential cryptanalysis in a very short period of time. Earlier this year, a biclique attack for FUTURE was published. We show in this paper, a biclique attack that is better than the one previously published, both in time, memory and data complexities, obtained through semi-automatic search and bicliques based on distinct generator sets. It requires 2 125.18 full computations of the cipher to run, while requiring only 2 20 data pairs and negligible memory. Prior to June of this year when an integral attack on FUTURE was published, it was also the fastest attack without using the full code-book of data. Still, when compared to it, our attack uses much less data while being only slightly slower, which presents a good trade-off.